IMPLEMENTASI MEDIA BIG BOOK DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS II SDN 008 SAMARINDA ILIR - Ellena Clarisa Sihombing; Hety Diana Septika; Muh. Ramli Buhari; Muhlis; Ridwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research began with the use of a learning media in the form of a big book, which is an interesting type of teaching media. The purpose of this research is to determine: (1) how the planning of the implementation of big book media in Indonesian language learning is carried out, (2) how the implementation of big book media in Indonesian language learning is conducted, and (3) how the evaluation of the implementation of big book media in Indonesian language learning in class II A SDN 008 Samarinda Ilir is performed. This research uses a qualitative approach with a descriptive type. The subjects of the study consist of the class teacher and students of class II A SDN 008 Samarinda Ilir. The research was conducted over 4 days, with 2 days for preliminary research and 2 days for the actual implementation. The data collection techniques used were observation, interviews, and documentation, with instruments including observation sheets for teacher activities, interview sheets, and documentation. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this study are: (1) The planning done by the teacher in Indonesian language learning includes preparing teaching modules and creating an interesting big book media, as well as making questions related to the big book; (2) The implementation of Indonesian language learning using the big book media involved the teacher reading the story from the big book and engaging students in dialogue throughout the lesson. There were also some challenges in the implementation, such as some students being less active and noisy; (3) The evaluation of the Indonesian language learning involved the teacher assigning questions related to the material in the big book, with the teacher providing 5 questions related to the story in the big book, and the students completing the questions on paper.